Learning path : SQL for business users. - Vaccaro, Guy; Blaha, Michael; Gilmore, W. J.; Higbee, Wes; Saternos, Casimir; Hanlon, Tom; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2016)
"Business users and analysts want quick, practical knowledge. Regarding SQL and database topics, they are more interested in how to use data rather than create it (this means the SELECT statement is highly relevant to them). As they progress they will likely want to know how to create their own databases, but only to a certain extent. The business logic of database design is likely what they are interested in. They may want to understand basic table design principles and a high-level understanding of normalization. But security, administration, data theory, and other DBA/engineering tasks will likely not be relevant to them. Typically when business users prototype a database for their business needs, they might hand it off to a DBA to put in production if it is deemed critical for the business."--Resource description page.
Getting started with databases and SQL / Guy Vaccaro -- Relational database management system (RDBMS) / Guy Vaccaro -- Data modelling / Michael Blaha -- Introducing MySQL / W. Jason Gilmore -- Up and running with Microsoft SQL Server / Wes Higbee -- Understanding SQL and R / Casimir Saternos -- Introduction to Apache Phoenix / Tom Hanlon.
Presenters, Guy Vaccaro, Michael Blaha, W. Jason Gilmore, Wes Higbee, Casimir Saternos, Tom Hanlon.
Title and publication information from resource description page (Safari, viewed January 11, 2017).
Keywords: SQL (Computer program language); Relational databases; MySQL (Electronic resource); SQL server; Electronic books